Blind liver biopsy: a 17-year experience - Urganci, Nafiye (2020)
Objectives: Liver biopsy is the gold standard for assessing liver inflammation, necrosis and fibrosis. The aim of the study is to evaluate clinical indications and histopathological results of percutaneus liver biopsy. Materials and methods: A total of 516 children who underwent blind liver biopsy were evaluated retrospectively. Results: Blind liver biopsy was performed for chronic active hepatitis B in 50% of the cases (n=260), neonatal cholestasis in 14% (n=68), autoimmune hepatitis in 7.7% (n=40), Wilson disease in 7.3% (n=38), isolated elevation of the liver enzymes in 5% (n=26), chronic active hepatitis C in 4.2% (n=22), metabolic disease in 3.4% (n=17), malignancies in 2.2% (n=11) and the others in 3.4% (n=17). Major complications were observed in 0.19% of the cases (n=1) and minor complications such as pain at the biopsy site in 13.5% of the cases (n=70), hypotension and tachycardia in 1.9% (n=10). Conclusions: Blind liver biopsy is a safe method in diagnosing liver diseases in childhood.